Mantle source heterogeneity of the Early Jurassic basalt of eastern North America - Gregory Shellnutt, J.; Dostal, Jaroslav; Yeh, Meng-Wan (International journal of earth sciences : Geologische Rundschau, 2018)
One of the defining characteristics of the basaltic rocks from the Early Jurassic Eastern North America (ENA) sub-province of the Central Atlantic Magmatic Province (CAMP) is the systematic compositional variation from South to North. Moreover, the tectono-thermal regime of the CAMP is debated as it demonstrates geological and structural characteristics (size, radial dyke pattern) that are commonly associated with mantle plume-derived mafic continental large igneous provinces but is considered to be unrelated to a plume. Mantle potential temperature ( T P ) estimates of the northern-most CAMP flood basalts (North Mountain basalt, Fundy Basin) indicate that they were likely produced under a thermal regime ( T P ≈ 1450 °C) that is closer to ambient mantle ( T P ≈ 1400 °C) conditions and are indistinguishable from other regions of the ENA sub-province ( T Psouth = 1320–1490 °C, T Pnorth = 1390–1480 °C). The regional mantle potential temperatures are consistent along the 3000-km-long ENA sub-province suggesting that the CAMP was unlikely to be generated by a mantle plume. Furthermore, the mantle potential temperature calculation using the rocks from the Northern Appalachians favors an Fe-rich mantle (FeOt = 8.6 wt %) source, whereas the rocks from the South Appalachians favor a less Fe-rich (FeOt = 8.3 wt %) source. The results indicate that the spatial-compositional variation of the ENA basaltic rocks is likely related to differing amounts of melting of mantle sources that reflect the uniqueness of their regional accreted terranes (Carolinia and West Avalonia) and their post-accretion, pre-rift structural histories.